Experimental and numerical studies of the vortex-induced vibration behavior of an asymmetrical composite beam bridge. Issue 10 (July 2019) - Wang, JX; Ma, CM; LI, Mingshui; Yeung, N; LI, Shaopeng
The vortex-induced vibration behavior and mechanism of an asymmetrical composite beam cable-stayed bridge is investigated by means of aerodynamic sectional tests and computational fluid dynamics methods. Tests are performed for the bridge deck under five wind attack angles (0°, ±2.5°, and ±5°) and two wind directions (0° and 180°) during the completion and construction stages. The influence of damping ratios, wind barriers, and vehicles on the vortex-induced vibration behaviors of the bridge deck is examined. The test and simulation results show that the properties of the vortex-induced vibrations vary with the wind direction as a result of the asymmetry of the main girder. The vertical maximum vortex-induced vibration amplitude of the bridge deck was found to occur at the wind attack angle of −5° and wind direction of 180°, while the torsional maximum was found at the wind attack angle of −5° and wind direction of 0°. Both vehicles and wind barriers have amplification effects on the vortex-induced vibrations of the bridge deck when the wind direction is 180°. The vortex-induced vibration of the bridge deck can be effectively mitigated when the damping ratio increases from 0.5% to 1.5%. The vortex-induced vibration mechanism of the bridge deck under different wind directions can be attributed to the same vortex shedding mode (the Kelvin–Helmholtz vortex and the Kármán vortex street). While, the location of the vortex generation and direction of the vortex shedding at the wake are strongly influenced by the wind directions, resulting in the variation of the vortex-induced vibration properties of the bridge deck with the wind direction. This study provides a guideline for the design of bridges with asymmetrical main girders to suppress the VIV.